(untitled) (Research, Society and Development, 2021)
Affection promotes transformations in education, allowing to stimulate pleasure during learning, favoring the child to better adapt to the environment, and its insertion as a pedagogical practice becomes necessary. The aim of this study was to investigate the importance of affectivity in early childhood education. This is a narrative, descriptive and exploratory bibliographic review. Based on the theme "Affectivity as a methodological practice in early childhood education: a narrative review", he formulated the following guiding question: What is the importance of affectivity as a methodological practice in teaching children? And online research databases such as ScieLO, ERIC, Google Scholar were consulted. In all, nineteen articles (19) were selected, according to the inclusion and exclusion criteria. The studies addressed the concepts of affectivity and its relationship with teaching, affectivity in the family context, the role of the teacher in the use of affectivity in the classroom, and the importance of affectivity in the teaching of early childhood education for the development and learning of children. kids. Affection must be seen as a practical approach in teaching children as a positive strategy in the learning process, strategies that can be developed by the teacher in the school environment, and also in the family context, as the bond between the student and his family provides benefits as for sociability and learning.